A study on the types of disaster awareness in nursing students: Q methodology - Mihyeon Seong; Dajung Ryu; Sohyune Sok (BMC, 2023)
Abstract Background Research for the development of nursing education strategies to enhance the competency of the nursing students on disaster safety are needed. This study aimed to identify the types of perceptions on disaster safety in nursing students, and to analyze and describe the characteristics of each type of disaster safety perception of nursing students in South Korea. Methods An exploratory study design applying Q methodology, a research method designed to study subjectivity. Participants were 30 nursing students in their 20s who are living in C city. This P-set was selected to best reveal the disaster safety awareness of nursing students. Participants provided their subjective viewpoints by sorting 30 statements into a grid. Analyses involved correlation and factor analysis. The study was carried out from June to December, 2020. Results In this study, four types of disaster safety awareness of nursing students were uncovered. The characteristics of each type were confirmed as follows: Type 1 was national responsibility, type 2 was individual responsibility, type 3 was preparedness-oriented, and type 4 was education-oriented. Conclusion This study shows that the types of perceptions on disaster safety in Korean nursing students were national responsibility, individual responsibility, preparedness-oriented, and education-oriented. The findings from this study can be implied as fundamental data in nursing education of disaster safety.